PELAKSANAAN KEGIATAN EKSTRAKURIKULER PADUAN SUARA DI SMK NEGERI 2 PADANG - Dinda Kamara; Yensharti Yensharti; Syeilendra Syeilendra (SENDRATASIK UNP, 2018)
AbstractThis article aims to describe the implementation of extracurricular choirs in SMK N 2 field. The cornerstone of the theory used in this study are: (1) implementation of extra-curricular activities choir. This research is qualitative research with the descriptive approach. This research was conducted in the field — 2. Data obtained from the results of the observation/observation and interview at SMK N 2 field. Research instrument is the researchers themselves as supporting instruments namely observation, notebooks and stationery, photo camera/mobile phone, and notes about the extracurricular choirs. Research results explain that through extra-curricular activities choir students are able to develop their talents and interests they have, because of the extracurricular activities is one of the extracurricular activities of the first chorus time held at SMK N 2 field. The implementation of extracurricular activities carried out on Fridays and Saturdays 13:40 exercise was carried out after hours of instruction completed this exercise is divided into two schedules latihanya it penggulangan exercise and workout staple material. Keywords: Implementation, Extracurricular, Chorus